Μ‐Opioid activation in the prefrontal cortex in migraine attacks – brief report I. (1st June 2014) - DaSilva, Alexandre F.; Nascimento, Thiago D.; DosSantos, Marcos F.; Lucas, Sarah; van Holsbeeck, Hendrik; DeBoer, Misty; Maslowski, Eric; Love, Tiffany; Martikainen, Ilkka K.; Koeppe, Robert A.; Smith, Yolanda R.; Zubieta, Jon‐Kar
Abstract We evaluated in vivo the μ‐opioid system during spontaneous episodic migraine headaches. Seven patients were scanned at different phases of their migraine using positron emission tomography with the selective μ‐opioid receptor (μOR) radiotracer [11C]carfentanil. In the ictal phase, there was μOR activation in the medial prefrontal cortex, which was strongly associated with the μOR availability level during the interictal phase. Furthermore, μ‐opioid binding changes showed moderate negative correlation with the combined extension and severity of the attacks. These results indicate for the first time that there is high μOR activation in the migraineurs' brains during headache attacks in response to their pain.